EFFECT OF JOB INVOLVEMENT AND SUPPORT ORGANIZATION SUPPORT TO EMPLOYEE PERFORMANCE WITH WORK SATISFACTION AS INTERVENING VARIABLES IN THE DIVISION OF HR AND FINANCE PT. PORTS TANJUNG PRIOK, JAKARTA - Lukiyana, Qhoirunnisa Sajdah (Prodi Pendidikan Administrasi Perkantoran UNIMED, 2019)
This study aims to determine to determine the effect of work involvement on employee performance through job satisfaction and to determine the effect of organizational support perceived employee to the performance of employees through job satisfaction in the Division of Human Resources and Finance PT. Port of Tanjung Priok, Jakarta. This research uses quantitative approach with data collection technique using questionnaire method. The population used in this research is all employees in the Division of Human Resources and Finance PT. Port of Tanjung Priok, Jakarta, amounting to 43 employees, while the sampling method using non-probability sampling technique. The free variable in this research is job involvement and organizational support, intervening variable in this research job satisfaction. While the dependent variable is employee performance. Data analysis technique used in this research using SEM model with partial least square approach (PLS) 3.0. From result of research of work involvement have an effect on signifikan to employee performance. This proves that the first hypothesis (H1) is accepted. Job involvement has a significant effect on job satisfaction. This proves that the second hypothesis (H2) is accepted. Organizational support has a significant effect on employee performance. This proves that the third hypothesis (H3) is accepted. Organizational support has a significant effect on job satisfaction. This proves that the fourth hypothesis (H4) is accepted. Job satisfaction has a significant effect on employee performance. This proves that the fifth hypothesis (H5) is accepted. Job involvement has a significant effect on employee performance through job satisfaction. This proves that the sixth hypothesis (H6) is accepted. Organizational support affects employee performance through job satisfaction. This proves that the seventh hypothesis (H7) is accepted.